POPULASI SERANGGA PADA TANAMAN CABAI (Capsicum annuum varlongum) DENGAN MENGGUNAKAN PUPUK ORGANIK DAN ANORGANIK DI DESA TONSEWER KECAMATAN TOMPASO DUA - Natalia Samba; Jantje Pelealu; Christina Salaki; Henny V.G. Makal (COCOS, 2014)
ABSTRACTThe research was conducted in the village of Subdistrict Tonsewer Tompaso Two for three months ie from July to October 2013. Laboratory studies conducted at the Laboratory of Entomology, Faculty of Agriculture and Plant Pests and field Unsrat Manado which is in District Tompaso. Land used for the observation that the land already planted chili farmers. The land area is used for observation of 15 x 3 m plots consisting of 6 which is then divided by three beds for the treatment of organic fertilizer and inorganic fertilizer plots 3 and 3 Plots for chemical fertilizers and each plot containing 22 tress chili plants. . In studies conducted at the plant chili with organic and inorganic fertilizer use are the following pests: Insects that bersosiasi on pepper plants that use organic and inorganic fertilizers, namely the Order Hymenoptera (vespidae family, Family: ichneuimonidae), Arachnida Order (family Araneidae), the Order Diptera (family Tephridae), Order Hemiptera (family: Alydidae), Order Coleopteran (family: Scarabidae) Order Homoptera (family: Aleyrodidae), Order Lepidoptera (family: Noctuidae), Aphids and Insects-Insects that dominate the area pepper plants that use organic fertilizers and inorganic fertilizers are Diptera (family Tepridae), Aphids (Family Aphididae) and Coleoptera (family Scarabidae). In this study there are enemies - namely natural enemies encountered spiders, and seranga - Insects such as Bemisia tabaci vectorKeywords : insect populations, chilli, Organic And Inorganic Fertilizers .